2012
DOI: 10.1371/journal.pone.0041688
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Regulation of the Synaptic Plasticity-Related Gene Arc

Abstract: Expression of activity-regulated cytoskeleton associated protein (Arc) is crucial for diverse types of experience-dependent synaptic plasticity and long-term memory in mammals. However, the mechanisms governing Arc-specific translation are little understood. Here, we asked whether Arc translation is regulated by microRNAs. Bioinformatic analysis predicted numerous candidate miRNA binding sites within the Arc 3′-untranslated region (UTR). Transfection of the corresponding microRNAs in human embryonic kidney cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 74 publications
6
67
2
1
Order By: Relevance
“…Consistent with these notions, inducing LTP or LTD rapidly alters the levels of many different miRNAs in hippocampal neurons (Park and Tang, 2009;Wibrand et al, 2010). MiRNAs affect synaptic plasticity by directly targeting synaptic receptors or their downstream targets (Dutta et al, 2013;Fiore et al, 2014;Kocerha et al, 2009;Letellier et al, 2014;Saba et al, 2012;Schratt et al, 2006), including LTD proteins such as Arc and Map1b (Chen and Shen, 2013;Wibrand et al, 2012). These findings suggest that variation in miRNA expression affects synaptic protein levels and, consequently, synaptic plasticity by controlling the stability and translation of dendritically localized transcripts.…”
Section: Introductionmentioning
confidence: 57%
“…Consistent with these notions, inducing LTP or LTD rapidly alters the levels of many different miRNAs in hippocampal neurons (Park and Tang, 2009;Wibrand et al, 2010). MiRNAs affect synaptic plasticity by directly targeting synaptic receptors or their downstream targets (Dutta et al, 2013;Fiore et al, 2014;Kocerha et al, 2009;Letellier et al, 2014;Saba et al, 2012;Schratt et al, 2006), including LTD proteins such as Arc and Map1b (Chen and Shen, 2013;Wibrand et al, 2012). These findings suggest that variation in miRNA expression affects synaptic protein levels and, consequently, synaptic plasticity by controlling the stability and translation of dendritically localized transcripts.…”
Section: Introductionmentioning
confidence: 57%
“…Treatment with LNA antisense oligonucleotides decreased the levels of miR-21 in glioblastoma cell lines [132] and miR-219 in cortex [128,133]. Similarly, peptide nucleic acids (PNAs) delivered into neurons decreased miR-326 activity and caused an increase in expression of synaptic plasticity genes [134].…”
Section: Microrna Therapymentioning
confidence: 99%
“…miR-34a regulates, on the other hand, SIRT1 in the context of neuronal stem-cell differentiation (Aranha et al 2011). A recent study has identified miR-34a as one of three miRNAs that cooperates in regulation of the Arc 3 ′ UTR and which inhibits endogenous Arc protein expression in neurons (Wibrand et al 2012).…”
Section: Differences Between Ca1 and Dgmentioning
confidence: 99%